Intellectual Capital and the Financial Performance of Banks in Bahrain (Journal of Business Management and Accounting, 2011)
This study examines whether intellectual capital infl uenced the fi nancial performance of banks in Bahrain during the period 2005 to 2007. Pulic’s Value Added Intellectual Coeffi  cient  (VAIC)  was  used  as  the  effi  ciency  measure  of  intellectual  capital.  Two regression models were constructed to test if the overall VAIC, and each of its three components  (capital  employed  effi  ciency,  human  capital  effi ciency  and  structural capital effi ciency) affect banks’ performance. The results support the hypothesis that intellectual  capital  has  a  positive  impact  on  the  fi  nancial  performance  of  banks  in  Bahrain. In addition, when VAIC is classifi ed into its three major components, we fi nd that fi  nancial  performance  is  positively  associated  with  capital  employed  effi ciency (CEE)  and  human  capital  effi  ciency  (HCE).  However,  our  fi  ndings  fail  to  fi nd  any signifi  cant  association  between  structural  capital  effi  ciency  (SCE)  and  fi nancial performance  of  the  banks.  This  study  provides  an  understanding  of  the  infl uence  of intellectual capital on banks’ performance in an emerging economy, Bahrain, in which its  economic  vision  2030  emphasises  the  importance  of  human  capital,  knowledge,  innovations and other elements of intellectual capital in sustaining its economic growth.